More Than a Game: Musculoskeletal Injuries and a Key Role for the Physical Therapist in Esports. - MCGEE, CAITLIN; HWU, MATTHEW; NICHOLSON, LESLIE L.; HO, KEVIN K. N. (Journal of Orthopaedic & Sports Physical Therapy, 2021)
SYNOPSIS: The esports industry is growing exponentially: more viewers, more support, more money, and more players. Esports competitors require high-level cognitive function and dexterity. There is an increasing demand for physical therapists to manage esports-related musculo- skeletal injuries across all levels of play (amateur, semi-professional, professional). Clinicians have relied on general musculoskeletal principles and extrapolating research findings from other populations, including athletes, office workers, air traffic controllers, and musicians, to inform an evidence-based practice approach to assessing and managing injury in esports competitors. The physical demands of esports competitors are triple those of office workers, varying across esports games, platforms (computer, console, mobile), and levels of performance. We highlight the role of physical therapy in esports, the need for best-practice guidelines for musculoskeletal health care, the current research evidence, and the large research gaps in the field.